Non-Financial Human Resources Management Reporting Indicators in The Area of Sustainable Development - Izabela RÓŻAŃSKA-BIŃCZYK; Paweł ŁUCZAK (Communications of International Proceedings, 2024)
The paper explores the integration of sustainable development within Human Resource Management (HRM) practices, emphasizing the need for comprehensive non-financial reporting indicators. The authors examine how sustainable practices, aligned with Environmental, Social, and Governance (ESG) criteria, are becoming essential in evaluating a company’s societal and environmental impact beyond financial performance. They highlight the challenges associated with reporting social aspects, such as employee well-being, due to a lack of standardized metrics. To address this, the study proposes a set of metrics within HRM that can assess organizational commitment to sustainability in social areas. These metrics are categorized into five key areas: employee well-being and job satisfaction, training and skills development, equality and diversity, working conditions and employment flexibility, and talent management and succession planning. Each category provides measurable indicators for companies to evaluate and report their progress in promoting a sustainable work environment. The paper argues that integrating these metrics can enhance transparency and accountability in sustainability reporting, supporting a balanced approach to meeting economic goals alongside environmental and social responsibilities. This framework aids organizations in achieving long-term sustainability, responding to regulatory requirements, and satisfying growing stakeholder expectations for responsible business practices.
Keywords: HRM reporting; non-financial reporting; ESG; UE Directive.